Cultural secessionism of “Sandžak” and regional security - Antonic, Slobodan (Sociološki pregled, 2026)
The first part of the paper examines two examples of cultural secessionism from the region of Raška and Polimlje (“Sandžak”) – the introduction of the “Bosnian language” and the appeal to Bosniaks to boycott Santa Claus. The second part of the paper provides an overview of the autonomist demands (1991-2025) of the Bosniak elite from Stari Ras, which most often boil down to the desire to establish an autonomous state under the NATO protectorate. The third part of the paper analyzes irredentist claims to annex “Sandžak” to Bosnia and Herzegovina or Kosovo*. The real security risks arising from this ideology and cultural practice are also considered, not only to the territorial integrity of the Republic of Serbia, but also to peace in the region.